ADOPTING AI-DRIVEN DATA CULTURE IN ORGANIZATION: CHALLENGES AND OPPORTUNITIES FROM EMPLOYEES’ PERSPECTIVES - Patil, Harshal; Kulkarni, Abhay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Data functions as an organization’s growth engine fuel. In the age of digitalization, it is among the most precious resources. Organizations now use data-driven decision-making processes instead of product-centered ones. This is due to the fact that it projects more accurate, impartial, and objective predictions. IT companies have faced challenges over the years relating to big data, including security, accessibility, reuse, automation, and decision-making. So, a lot of businesses have concentrated on implementing AI-driven data culture. The purpose of this paper is to investigate the possibilities for establishing an AI-driven data culture in Pune’s IT/ITES companies. Additionally, it attempts to pinpoint the opportunities and difficulties associated with implementing an AI-driven data culture from the viewpoint of the workforce. Regression analysis was used to examine data from a survey of 200 participants from various organizational levels. The results show a substantial gender gap in perception, emphasizing the necessity for gender-specific adoption tactics for AI-driven data culture. Lack of advanced internal expertise, recurrent data use, inadequate infrastructure, restricted or nonexistent finance, and inadequate data management (quality, sources, validity, accessibility, approvals, execution, alignment with organisation goals, etc.) are a few of the main obstacles. Opportunities include standardization, automation, quality report generating, integration, and simplification. From the standpoint of process improvement, performance improvement, compliance, audits, trend analysis, and competitive analysis, the current study is noteworthy. It may result in long-term sustainable growth and the best possible use of available resources.